An obstacles to the Kurdish state under international law and policy - مەسعود عبدالخالق محمد ئەمین (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
There is a fundamental difference between those who divided Kurdistan (beginning of the twentieth century) with the continuation of the case so far, the first responsibility lies with colonialism and its objectives, while the second expands to the responsibility of regional and internal (the occupied state). Hence, the obstacles are intertwined to include political, legal and military aspects, which are beyond the scope of the Kurdish capabilities; all this has led to continuation of the Kurdish issue without the prospect of a solution. For that we need to form alliances in the Middle East and the world. Although, these alliances are not easy for entities that do not have states in fact, but it is not impossible. Indeed, historical moments and great opportunities have come several times to establish a Kurdish state, but due to lack of wisdom and sufficient knowledge of Kurdish leadership in terms of political and legal aspects so that has led to miss these opportunities. It should be noticed that there are still opportunities to turn the Kurdish issue from "right of secession" to "self-determination". This means the Kurdish issue has to be internationalized and one requirement for that is to build the Middle East reform project along with other international reform projects. Finally, in this study we precisely examined the internal, regional and international obstacles to the establishment of Kurdish state. The roadmap is based on international policy and international laws. These obstacles can be overcome and building a state without violating the sovereignty and interests of the peoples of the region. Rather, it will become the foundation factor for peace and brotherhood.